Pola Pergerakan Orang di Masa Pandemi dengan Pendekatan Eksploratif di Wilayah Kepulauan Bangka Belitung - Desy Yofianti; Revy Safitri (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
COVID-19 has spread around the world and has given a huge impact on people's lives. One of the changes in the COVID-19 condition is the travel pattern of people. Travel patterns can be explained in terms of the flow of vehicles, passengers, and people's mobility from the origin and destination zones within a certain area and period. On the other hand, it is known that travel patterns are an essential factor in solving transportation problems. The change of travel pattern data is needed for transportation planners and policymakers in providing safe transportation during the pandemic. In addition, data on travel patterns also play an important role in determining travel restrictions in an area to reduce the spread of COVID-19. This study tries to analyze travel patterns during the COVID-19 pandemic through an exploratory approach by taking a case study in the Bangka Belitung Province. The results of this study show that the mobility was dominated by intra-island trips during the pandemic, both within Bangka Island and Belitung Island. Furthermore, during the COVID-19 pandemic, the majority of people made changes to their routine's mobility. More than 50% of people did not return to their original travel patterns even though the pandemic conditions had entered the New Normal period. The most influential factor which makes people change their mobility is to take precautions from COVID-19.